A hybrid multiple criteria evaluation method of ranking of cultural heritage structures for renovation projects - Turskis, Zenonas; Morkunaite, Zydrune; Kutut, Vladislavas (International Journal of Strategic Property Management, 2017)
Cultural heritage item preservation, renovation and adaptation to the social needs of people, as well as their passing from generation to generation, is a problem relevant from economic, historical, archeological, religious, technological, research and other perspectives. They are typical strategic multi-criteria decision-making problems. The state institutions and the owners and managers of the heritage items invest in their preservation. In fact, every country has a great number of the registered heritage structures. To ensure their effective management and renovation, a lot of implementation projects and strategies should be developed and evaluated. This work requires large investments and time. The paper presents a hybrid model developed for ranking the heritage buildings intended for renovation according to their value. The model for problem solution based on integrated using two MCDM methods Analytic Hierarchy Process and EDAS. A set of the criteria for evaluating the projects, concerning the renovation of cultural heritage items defined.